Genes on syndromic and idiopathic CTEV: A systematic review - Muhammad, Hilmi (Elsevier Ltd, 2022)
Background: Congenital talipes equinovarus (CTEV), also known as clubfoot, is a common but understudied developmental disease of the lower limb. The cause of congenital clubfoot is unclear, and the role of environmental and genetic factors remains unknown. Idiopathic CTEV and syndromic CTEV have rather different clinical features, proposed etiopathogenetic mechanisms, and treatment options. This study aimed to provide an update on the genes involved in idiopathic and syndromic CTEV. Methods: We conducted this systematic review according to the guideline of the Preferred Reporting Items for Systematic Reviews and MetaAnalyses (PRISMA) 2020 Statement, only papers that have been published from the year 2019 until the search date was included. Three medical electronic databases (PubMed, Science Direct, and European PMC) were searched by a single author on October 24th, 2021. The titles and abstracts were screened where studies of any level of evidence reporting clinical or preclinical results published from 2019 onwards, mentioned gene(s) involved in cases presenting with CTEV (idiopathic and syndromic) were included. Data were synthesized with use of the Microsoft Excel (Microsoft, Redmond, WA). Results: Fifty-three studies were included and analyzed in this paper, which met all inclusion criteria (11 articles that discussed genes involved in the presence of isolated CTEV and 42 articles for syndromes with CTEV phenotypes). The top three individual genes mentioned were PITX1, MTHFR, and ZC4H2 for the idiopathic, also HOX D13, SLC 26A2, and TBX4 for the syndromic. The top three family genes related to CTEV were HOX family, CASP family, and COL family. According to the results, the most often involved in idiopathic CTEV is HOX gene. Including studies of any level of evidence reporting clinical or preclinical results that mentioned gene(s) involved in cases presenting with CTEV carries a greater risk of being due to multiple biases. High heterogeneity and the paucity of high-profile studies on the etiology of CTEV also sets a major limitation for this study. Conclusions: Genetic play a significant role in the etiopathogenesis of idiopathic and syndromic CTEV. PITX1 and MTHFR gene are the most frequently mentioned individual gene for idiopathic CTEV, whereas ZC4H2 gene being the most mentioned for syndromic CTEV. The HOX family genes were also found to be associated with both phenotypes.